2018
DOI: 10.3390/nu11010011
|View full text |Cite
|
Sign up to set email alerts
|

Low Phytanic Acid-Concentrated DHA Prevents Cognitive Deficit and Regulates Alzheimer Disease Mediators in an ApoE−/− Mice Experimental Model

Abstract: Alzheimer’s disease (AD) is the main cause of dementia and cognitive impairment. It has been associated with a significant diminution of omega-3 polyunsaturated fatty acid docosahexaenoic acid (DHA) levels in the brain. Clinical trials with DHA as a treatment in neurological diseases have shown inconsistent results. Previously, we reported that the presence of phytanic acid (PhA) in standard DHA compositions could be blunting DHA’s beneficial effects. Therefore, we aimed to analyze the effects of a low PhA-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…ω‐3 Polyunsaturated fatty acids have protective effects against central nervous system diseases, and high doses of DHA can reduce the risk of dementia among the elderly. [ 44 ]…”
Section: Discussionmentioning
confidence: 99%
“…ω‐3 Polyunsaturated fatty acids have protective effects against central nervous system diseases, and high doses of DHA can reduce the risk of dementia among the elderly. [ 44 ]…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the mechanism through which omega-3 supplement use stabilizes CBF, the consequent increased delivery of oxygen and nutrients to the brain could explain findings from other studies that show omega-3 fatty acids augment cognitive function and prevent cognitive decline [39][40][41][42]. For example, the connection between atherosclerosis and dementia has been well-established [43], and a meta-analysis of randomized controlled trials showed that omega-3 fatty acids significantly slowed the progression of atherosclerosis [44], suggesting that omega-3 fatty acids could potentially prevent cognitive decline through improvements in vascular health.…”
Section: Discussionmentioning
confidence: 99%